How drawings work a user-friendly theory - Piedmont-Palladino, Susan C. (Routledge/Taylor & Francis Group, 2019)
"How Drawings Work cheekily explains that what architects make is information that enables other people to make buildings. That information comes in a variety of forms: drawings by hand and computer, models both physical and virtual, and words as needed. The book reflects in witty prose on the nature of architectural drawings as tools of communication, pulling from a diverse and eclectic landscape of theories from grammar, functional linguistics, philosophy, art criticism, science fiction, popular culture, and, of course, architecture, to propose a new way to think about architectural communication."--